The impact of service quality on parental satisfaction: evidence from private schools in Selangor - Gopal Rajadurai, Kanesh Gopal; Jan, Muhammad Tahir (2017)
This study analyses the features of Service Quality that could impact the satisfaction of parents whose children patronize private schools in the state of Selangor, Malaysia. This study adapts the SERVQUAL model to measure service quality evident in private schools, and uses Structural Equation Modelling (SEM) to evaluate the relationship between Service Quality and Parental Satisfaction. This research utilizes a quantitative technique, with a Likert scale questionnaire, that was created by adapting the SERVQUAL measurement tool, as well as by reviewing past literature. Data was collected from selected private schools in Selangor, and further analysed using SPSS and AMOS software. This study had a total of 411 respondents, from 8 varying private schools. During data analysis, reliability tests were conducted followed by factor analysis and then structural equation modelling in order to test the hypotheses. The results indicated that two aspects of Service Quality, namely Tangibility and Responsiveness seem to effect the satisfaction of parents in private schools. This study implies that private school administrators should focus on aspects of Tangibility and Responsiveness, in order to have a larger impact on parental satisfaction.